KONSTRUKSI IDENTITAS MUSLIM DI MEDIA BARU - Rulli Nasrullah (Fakultas Dakwah UIN Prof. K.H. Saifuddin Zuhri, 2011)
1n his book, The Question of Cultural Identity, Stuart Hall states that the inventions inthis modern era has brought a new development and transformed the concept of individualism.It deals with the concept of an individual as a subject and how the identity of an individualworks. In this modern era, there is a transformation among individuals by which they try tofree themselves from the traditions and social cultures that have restricted them. In fact, theconcept of individualism does not merely occur in this modern era but it had also occurred inpre-modern era. However, this term differs in its life, experience, and concepts.One of the characteristics of modernity which is supposed to change the existing socialstructure, according to Hall, is the invention and the development of machines and theinvention of internet which leads to virtual culture. One example is that the presence offacebook account of Everybody Draw Mohammed Day has resulted in a protest from Muslimsfrom all over the world. As a result, this protest has led to the presence of competitor sitesimilar to facebook. This fact shows that the expression of Muslim identity in virtual world orinternet plays an important role on the formation of self identity, which Michel Foucault calledthe formation of Muslim identity discourse.